Pola Asuh Orang Tua dalam Pembelajaran Daring Selama COVID-19 - Rury Prissa Sonnie (Ridwan Institute, 2021)
Covid-19 is an outbreak that is almost infecting the whole world including Indonesia. Until January 2021, almost 1 million people were declared positive for Covid-19. With the Covid-19 outbreak, there are many changes in almost all elements in the community. Not only in the field of health, economy, social but also in the field of education. With the issuance of the Regulation of the Ministry of Education so that online learning is enforced for school-age children. Therefore, it takes the role of parents in the education of the child by applying the right parenting patterns for the child during home study. This study uses qualitative research, sampling with purposive sampling that is parents who have school-age children. Data collection techniques with observations and interviews. In online learning parents apply a pattern of autocracy, democracy and permissive parenting. But by changing the way children learn from home school, of course, not all parents can apply a good parenting pattern for the child because of the demands of working parents. Therefore, to be able to provide motivation for children in learning parents need to provide a sense of security, comfortable in learning children, provide rewards and still communicate to children in between busy parents work.